Entrepreneurship Curriculum Development in Senior High School - Chaerudin, Rendra; Hartati, Sri (International Journal of Engineering and Technology, 2018)
Entrepreneurship-based education is education that applies principles and methodology to the internalization of values in learners through a curriculum integrated with the development that occurs both in the school environment and community environment and the use of learning models and strategies relevant to the purpose of learning itself. The values developed in entrepreneurship education are the development of entrepreneurial values and competencies that reflect a successful entrepreneur.The entrepreneurial competencies to be built through the entrepreneurship curriculum at high school include a group of knowledge, Â Â Â attitudes, and skills acquired and used by individuals simultaneously, to produce outstanding performance in the field of entrepreneurship. Entrepreneurial knowledge is knowledge structure that an entrepreneur uses to make judgments or take decisions involving opportunity evaluation, business creation and growth. Knowledge is the scope of the cognitive domain of competence skills that students must Â Â Â Â Â possess. An entrepreneur must have business-related skills. Some of the skills that need to be possessed include conceptual skills inÂ Â managing strategies and taking into account risks, creative skills in creating added value, skills in leading and managing, communication and interaction skills, and technical skills in the field of business undertaken. Entrepreneurship education when done intensively can shape the mindset, skills and attitudes / behavior of high school students.This research showed that simultaneously the variables of knowledge, skill, and attitude have positive and significant influence to Â Â Â Â Â Entrepreneurial competence in entrepreneurship curriculum at high school. Furthermore, the test results partially indicate that each variable of knowledge, skill, and attitude have positive and significant influence to Entrepreneurial competence in entrepreneurship curriculum at high school.Â Â